A consciência espiritual na educação interdisciplinar - Godoy, Herminia Prado (2011)
This work discusses the widening of spiritual consciousness as a means of creating an interdisciplinary education. The method used was the interdisciplinary investigation through narrative, reactivating the written, spoken and socialized memory. The Data from my own clinic experiences, which resulted in transformations and radical changes in my consciousness, were processed. Well-pondered observations, made during interdisciplinary classes, taught by Fazenda between 2008 and 2010, were catalogued. A careful research of written works, dissertations and thesis, oriented by Fazenda between 1986 and 2010, was accomplished. Twenty-one questionaries that were taken by my Education/Curriculum Program classmates during 2008's first semester were also charted. Three fundamental questions have permeated this investigation: The first was the conceptualization of the meaning of spirituality; the second dealt with spirituality within the Brazilian Educational Context and the third, sought answers for what does the interdisciplinarity, lived, practiced and theorized by Fazenda actually means, and how it is related to spirituality. I verified that Fazenda's interdisciplinary activity resembles the work of a "consciousness therapist", this way; spirituality is intrinsic to the interdisciplinary education which performs. Considering spirituality as one of the principles of interdisciplinarity, could reveal that the search for spirituality contemplates the following principles: waiting, detachment, humility, respect and consistency. Interdisciplinarity thus would be an openness vector to spirituality and the interdisciplinary educator, a "consciousness therapist"